2017
DOI: 10.1016/j.coi.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Obesity altered T cell metabolism and the response to infection

Abstract: An epidemic of obesity over the past three decades increases the risk of chronic and infectious diseases for adults and children alike. Within the past few years, obesity has been shown to impair the adaptive immune response to infection through alterations in T cell functioning. Growing evidence suggests that perturbations in T cell metabolism drives this stunted immune response, stemming from nutrient, hormone and adipokine dysregulation in the obese. In this review, recent findings in the fields of obesity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 59 publications
0
61
0
5
Order By: Relevance
“…Many factors that could potentially impact the immune response are impaired in obesity, including increased leptin concentrations, altered immune cell metabolism, and epigenetic factors, and may therefore underlie the impaired immune response to infectious disease in obesity [39]. Intriguingly, a growing body of evidence supports the notion that impaired immunological responses to infection in people living with obesity are driven by perturbations in T cell activation and function [35]. Interestingly, recent studies have demonstrated that the innate immune system, like the adaptive immune system, is able to adopt a long-term activated phenotype by previous encounters with microbial stimuli, leading to an increased immune response upon secondary stimulation ("trained innate immunity") [34].…”
Section: Immunological Alterations In Obesitymentioning
confidence: 99%
“…Many factors that could potentially impact the immune response are impaired in obesity, including increased leptin concentrations, altered immune cell metabolism, and epigenetic factors, and may therefore underlie the impaired immune response to infectious disease in obesity [39]. Intriguingly, a growing body of evidence supports the notion that impaired immunological responses to infection in people living with obesity are driven by perturbations in T cell activation and function [35]. Interestingly, recent studies have demonstrated that the innate immune system, like the adaptive immune system, is able to adopt a long-term activated phenotype by previous encounters with microbial stimuli, leading to an increased immune response upon secondary stimulation ("trained innate immunity") [34].…”
Section: Immunological Alterations In Obesitymentioning
confidence: 99%
“…glucose, fatty acids, etc.) [7,8]. In addition, checkpoint blockade therapies aimed at reinvigorating exhausted T cell responses are showing great promise in treating cancer patients in the clinic [9].…”
Section: Introductionmentioning
confidence: 99%
“…It may seem counterintuitive that COVID-19, a communicable disease, has such contiguity with non-communicable diseases such as obesity. However, people with obesity have an elevated risk of hospitalization, serious illness, and mortality, likely due to chronic lowgrade inflammation [1], an altered immune response to infection, as well as related cardiometabolic comorbidities [2], and the COVID-19 pandemic is likely to have a significant impact on people with obesity. The lockdowns imposed by many countries, combined with extensive efforts to isolate both vulnerable populations and people with diagnosed or suspected COVID-19 and to quarantine potential contacts, have many consequences for health behaviours and well-being.…”
mentioning
confidence: 99%